2010
DOI: 10.1258/ebm.2010.010136
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of self-sequential longitudinal reference intervals of maternal thyroid function during pregnancy

Abstract: The objective of this study is to establish self-sequential longitudinal reference intervals of thyroid function in normal pregnant women. According to the selection criteria, 301 cases were taken as the normal pregnant population to establish a normal reference range. Meanwhile, 150 healthy women were selected as the normal non-pregnant control group. To establish their own self-sequential longitudinal reference intervals, we collected samples five times in every case throughout the gestation (including first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 19 publications
4
19
0
1
Order By: Relevance
“…In similar studies, on Indian pregnant women using similar analytic methods, the TSH values usually had higher normal limits compared to our results [18], while a study is done in China showed comparable results to ours, especially in early pregnancy [24]. …”
Section: Discussionsupporting
confidence: 85%
“…In similar studies, on Indian pregnant women using similar analytic methods, the TSH values usually had higher normal limits compared to our results [18], while a study is done in China showed comparable results to ours, especially in early pregnancy [24]. …”
Section: Discussionsupporting
confidence: 85%
“…However studies by Marwaha et al in India [16] and Dhatt et al in the United Arab Emirates [21] reported much higher TSH upper reference values than the present survey. Our TSH reference limits approximate those of Yu et al from China [14], who used the same self-sequential design; we, however, used the 5th and 95th percentiles as the reference limits instead of the 2.5th and 97.5th used in their study. In agreement with previous studies our results indicate that the derived reference intervals of TSH for pregnant women were different (narrower and lower) from those proposed by kit manufacturers (0.2–4.5 mIU/L).…”
Section: Discussionmentioning
confidence: 99%
“…Existing results are inconsistent and should not be extrapolated due to differences in ethnicity, maternal iodine status, laboratory assay method, and rigor for selection of reference population (choice of reference population, sample size, assessment of outliers, and so forth). There is also a doubt about the validity of the results as data are mostly derived from earlier studies [7], cross-sectional studies restricted to one trimester [811], use of less accurate hormone assays techniques, studies on population with differing iodine status [12, 13], applying outdated statistical methods for calculating reference ranges, and cross-sectional studies on different women from different gestations instead of longitudinal self-sequential surveys [12, 14]. Estimating self-sequential reference intervals [14] has narrower variations than interindividual variations caused by sampling error in cross-sectional studies conducted on different groups and hence provides clinicians with more accurate values for proper diagnoses and management.…”
Section: Introductionmentioning
confidence: 99%
“…This, however, was a combination of cross-sectional samples as well as longitudinal samples from the same patients. 18 In 2010, Yu et al 19 calculated longitudinal reference intervals in the Chinese population and demonstrated narrower intervals compared to other studies. Cotzias et al in 2007 also reported cross-sectional reference intervals.…”
Section: Introductionmentioning
confidence: 99%